MiR-103a-3p regulates mitophagy in Parkinson's disease through Parkin/Ambra1 signaling. (October 2020) - Zhou, Junjun; Zhao, Yan; Li, Zhenlu; Zhu, Meiyang; Wang, Zhecheng; Li, Yang; Xu, Ting; Feng, Dongcheng; Zhang, Su; Tang, Fan; Yao, Jihong
Graphical abstract: Highlights: miR-103a-3p suppressed Parkin expression by targeting 3'-UTR of Parkin mRNA. miR-103a-3p inhibition has neuroprotective effects in PD. Parkin/Ambra1-mediated mitophagy may be involved in the mechanism of miR-103a-3p. Abstract: Parkin is a crucial protein that promotes the clearance of damaged mitochondria via mitophagy in neuron, and parkin mutations result in autosomal-recessive Parkinson's disease (AR-PD). However, the exact mechanisms underlying the regulation of Parkin-mediated mitophagy in PD remain unclear. In this study, PD models were generated through incubation of SH-SY5Y cells with 1-methyl-4-phenylpyridinium ion (MPP +, 1.5 mM for 24 h) and intraperitoneal injections of 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP, 30 mg/kg for five consecutive days) in mice. A Bioinformatics database was used to identify Parkin-targeting microRNAs (miRNAs). Then, miR-103a-3p agomir, miR-103a-3p antagomir and Parkin siRNA were used to assess the effects of miR-103a-3p/Parkin/Ambra1 signaling-mediated mitophagy in PD in vitro and in vivo . The protein and mRNA levels of Parkin and Ambra1 were significantly decreased, while miR-103a-3p, which is a highly expressed miRNA in the human brain, was obviously increased in PD mouse and SH-SY5Y cell models. Moreover, miR-103a-3p suppressed Parkin expression by targeting a conserved binding site in the 3'-untranslated region (UTR) of Parkin mRNA. Importantly, miR-103a-3p inhibition resulted in neuroprotective effects and improved mitophagy in vitro and in vivo, whereas Parkin siRNA strongly abolished these effects. These findings suggested that miR-103a-3p inhibition has neuroprotective effects in PD, which may be involved in regulating mitophagy through the Parkin/Ambra1 pathway. Modulating miR-103a-3p levels may be an applicable therapeutic strategy for PD.